APPLICATION OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) LEARNING MODEL IN ELEMENTARY SCHOOL SCIENCE LEARNING - Sukma nur amini; Zakia Kharinaa; Windy Herdiyanti. P (CV Grasta Glory, 2026)
The implementation of this research aims to improve students' knowledge and learning outcomes after the introduction of the contextual teaching and learning (CTL) learning model to the learning process. The purpose of learning using this model is to improve student learning achievement in 2024/2025. The author seeks to find out what learning outcomes students achieve through contextual teaching and learning (CTL) from previous learning. Based on our experience, students' interest in learning is low because teachers only use lecture and question-and-answer methods during learning. Teachers fail to carry out teaching and learning activities optimally. The primary issue is that teachers' learning processes do not fully contribute to enhancing students' academic achievement. In this case, the author tries to apply contextual teaching and learning (CTL) to the learning process in the classroom. In other words, implementing the contextual teaching and learning (CTL) model in the learning process is a crucial step towards enhancing student learning outcomes.